Development of the method for the optimal management of occupational risks - Bochkovskii, Аndrew; Gogunskii, Viktor (Eastern-European Journal of Enterprise Technologies, 2018)
Within the framework of this research, we analyzed international normative and legal documents on risk management in the field of occupational health and safety and identified the following shortcomings: – uncertainty of the aims of risk management; – complexity of performance of the appropriate procedure and its insufficient substantiation; – lack of available approaches to possibility of the optimal risk management, taking into consideration resource capacities of the business entity. It was noted that one of the main ways of occupational risks management is the reallocation of financial resources of an enterprise. However, based on the result of the analysis, the available methodological tools for implementation of this method were not detected. To solve this relevant problem, the method for optimal management of occupational risks was developed. The method was developed based on construction of the optimization models, based on the criteria of minimization of average estimated total costs of an enterprise for occupational safety and health. It was noted that harmful production factors operate with random intensity within the working zone over a period of time. And the risk is measured by the probability of exceeding permissible concentrations (levels) of certain factors, which operate in the workspace, as well as with relevant consequences. The variables of the developed models are costs of an enterprise for measures, related to ensuring safe and healthy working conditions. Direct and inverse optimization problems were stated that were reduced to certain problems of convex programming. The direct problem is to minimize probability of a risk event at the assigned constraint for total costs of occupational safety and health. The reverse problem is how to minimize the average costs for prevention and elimination of consequences of the risk of exceeding permissible concentration at constraint for probability of such excess. Calculation of the models identified dependence, which is expressed in a decrease in permissible probability of a risk event at an increase in costs of occupational safety and health. This makes it possible to recommend them for using by business entities in the international format.